Early Childhood Disaster Management Media Through Picture Story Books - Solfiah, Yeni Solfiah; Risma, Devi; Hukmi; Kurnia, Rita (Program Studi Magister Pendidikan Anak Usia Dini, 2020)
Indonesia is a country that has a high potential for natural disasters. Picture story book is a form of disaster management learning that can help children from an early age to prepare for a natural disaster. The aims of this study to develop story books as a disaster management learning media, to improve knowledge and skills of children and teacher about the understanding, principles, and actions of rescue when facing the natural disasters, to increase the teacher’s learning quality in disaster management. Developmental research approach is used to execute the study. A total of 48 children aged 5-6 years have to carry out pre-test and post-test. Pre-test data shows that children's knowledge about disaster management with an average of 47.92% and its improved at post-test with 76,88%. Five theme of story books involves floods, landslides, earthquakes, tsunamis, lands and forest fires is the product. Dissemination of five story books are proper for children and improve their understanding of disaster management. Keywords: Early Childhood Education, Management Disaster, Storybooks Reference: Abulnour, A. H. (2013). Towards efficient disaster management in Egypt. Housing and Building National Research Center. https://doi.org/10.1016/j.hbrcj.2013.07.004 Adiyoyoso, W. (2018). Manajemen Bencana. Jakarta: Bumi Aksara. Anderson, T., & Shattuck, J. (2012). Design-based research: A decade of progress in education research? Educational Researcher, 41(1), 16–25. https://doi.org/10.3102/0013189X11428813 Batič, J. (2019). Reading Picture Books in Preschool and Lower Grades of Primary School. Center for Educational Policy Studies Journal, (November), 1–18. https://doi.org/10.26529/cepsj.554 Bosschaart, A., van der Schee, J., Kuiper, W., & Schoonenboom, J. (2016). Evaluating a flood- risk education program in the Netherlands. Studies in Educational Evaluation, 50, 53–61. https://doi.org/10.1016/j.stueduc.2016.07.002 Codreanu, T. A., Celenza, A., & Jacobs, I. (2014). Does disaster education of teenagers translate into better survival knowledge, knowledge of skills, and adaptive behavioral change? A systematic literature review. Prehospital and Disaster Medicine, 29(6), 629–642. https://doi.org/10.1017/S1049023X14001083 Delicado, A., Rowland, J., Fonseca, S., & Nunes, A. (2017). Children in Disaster Risk Reduction in Portugal : Policies , Education , and ( Non ) Participation. 246–257. https://doi.org/10.1007/s13753-017-0138-5 Demiroz, F., & Haase, T. W. (2019). The concept of resilience: a bibliometric analysis of the emergency and disaster management literature. Local Government Studies, 45(3), 308–327. https://doi.org/10.1080/03003930.2018.1541796 Efthymis, L., Michael, S., Alexia, G., Panagiotis, P., Vassiliki, A., Kate, V., & Spyros, P. (2014). Disaster Data Centre — An Innovative Educational Tool for Disaster Reduction through Education in Schools. (September), 35–40. Faber, M. H., Giuliani, L., Revez, A., Jayasena, S., Sparf, J., & Mendez, J. M. (2014). Interdisciplinary Approach to Disaster Resilience Education and Research. Procedia Economics and Finance, 18(September), 601–609. https://doi.org/10.1016/s2212- 5671(14)00981-2 Frankenberg, E., Gillespie, T., Preston, S., Sikoki, B., & Thomas, D. (2011). Mortality, the family and the Indian Ocean Tsunami. Economic Journal, 121(554), 162–182. https://doi.org/10.1111/j.1468-0297.2011.02446.x Fujioka, T., & Sakakibara, Y. (2018). School education for disaster risk reduction in Japan after the 2011 Great East Japan Earthquake and Tsunami (GEJET). Terrae Didatica, 14(3), 313– 319. https://doi.org/10.20396/td.v14i3.8653531 Guha-Sapir, D., Van Panhuis, W. G., & Lagoutte, J. (2007). Short communication: Patterns of chronic and acute diseases after natural disasters - A study from the International Committee of the Red Cross field hospital in Banda Aceh after the 2004 Indian Ocean tsunami. Tropical Medicine and International Health, 12(11), 1338–1341. https://doi.org/10.1111/j.1365- 3156.2007.01932.x Haggstrom, M. (2020). The art of read-aloud, body language and identity construction: A multimodal interactional analysis of interaction between parent, child and picture book. International Journal of Language Studies, 14(1), 117–140. Halim, L., Abd Rahman, N., Zamri, R., & Mohtar, L. (2018). The roles of parents in cultivating children’s interest towards science learning and careers. Kasetsart Journal of Social Sciences, 39(2), 190–196. https://doi.org/10.1016/j.kjss.2017.05.001 Hamele, M., Gist, R. E., & Kissoon, N. (2019). P ro v i s i o n o f C a re f o r C r i t i c a l l y I l l C h i l d ren i n Disasters. 35, 659–675. https://doi.org/10.1016/j.ccc.2019.06.003 Justice, L. M., & Piasta, S. (2011). Developing children’s print knowledge through adult-child storybook reading interactions: Print referencing as an instructional practice. In Handbook of early literacy research (In S. B. N). Kitagawa, K. (2016). Situating preparedness education within public pedagogy. Pedagogy, Culture & Society, 1366(November), 1–13. https://doi.org/10.1080/14681366.2016.1200660 Kousky, C. (2016). Impacts of natural disasters on children. Future of Children, 26(1), 73–92. https://doi.org/10.1353/foc.2016.0004 Latif, M., Zukhairina, Zubaidah, R., & Afandi, M. (2013). Orientasi Baru Pendidikan Anak Usia Dini (Teori dan Aplikasi). Jakarta: Kencana Prenada Media Group. Lin, R. (2012). A Study of Curriculum Innovation Teaching and Creative Thinking for Picture Book Creation. IERI Procedia, Vol. 2, pp. 30–35. https://doi.org/10.1016/j.ieri.2012.06.047 Lopez, Y., Hayden, J., Cologon, K., & Hadley, F. (2012). Child participation and disaster risk reduction. International Journal of Early Years Education, 20(3), 300–308. https://doi.org/10.1080/09669760.2012.716712 Manjale, N. B., & Abel, C. (2017). Significance and adequacy of instructional media as perceived by primary school pupils and teachers in. 4(6), 151–157. Masuda, K., & Yamauchi, C. (2017). The effects of female education on adolescent pregnancy and child health: evidence from Uganda’s Universal Primary Education for fully treated cohorts. GRIPS Discussion Paper - National Graduate Institute for Policy Studies, (17/01), 49-pp. Retrieved from https://pdfs.semanticscholar.org/07f5/ebe91e3ac20179daae7d885ea50f8154f94e.pdf Mateo, R. M. (2015). Contrastive Multimodal Analysis of two Spanish translations of a picture book. 212, 230–236. https://doi.org/10.1016/j.sbspro.2015.11.338 McKenney, S., & Reeves, T. (2012). Conducting educational design research. London: Routledge. Meng, L., & Muñoz, M. (2016). Teachers’ perceptions of effective teaching: a comparative study of elementary school teachers from China and the USA. Educational Assessment, Evaluation and Accountability. Mudavanhu, Chipo Muzenda Manyena, B., & Collins, A. E. (2016). Disaster risk reduction knowledge among children in Muzarabani District, Zimbabwe. Natural Hazards, 84(2), 911–931. https://doi.org/10.1007/s11069-016-2465-z Mutch, C. (2014). International Journal of Educational Development The role of schools in disaster settings : Learning from the 2010 – 2011 New Zealand earthquakes. International Journal of Educational Development. https://doi.org/10.1016/j.ijedudev.2014.06.008 Ozturk, M. B., Sendogdu, M. C., Seker, E., & Tekinsen, H. K. (2011). Parents with children in preschool children ’ s picture book review elections. 15, 1906–1910. https://doi.org/10.1016/j.sbspro.2011.04.025 Peek, L. (2008). Children and Disasters: Understanding Vulnerability, Developing Capacities, and Promoting Resilience - An Introduction. Children, Youth and Environments, 18(1), 1– 29. Plomp, T., & Nieveen, N. (2007). An introduction to educational design research. Enschede: The Netherlands: SLO. Pramitasari, M., Yetti, E., & Hapidin. (2018). Pengembangan Media Sliding Book Untuk Media Pengenalan Sains Kehidupan (Life Science) Kelautan untuk Anak Usia Dini. Jurnal Pendidikan Usia Dini, 12(November), 281–290. Proulx, K., & Aboud, F. (2019). Disaster risk reduction in early childhood education: Effects on preschool quality and child outcomes. International Journal of Educational Development, 66(October 2017), 1–7. https://doi.org/10.1016/j.ijedudev.2019.01.007 Pyle, A., & Danniels, E. (2016). Using a picture book to gain assent in research with young children. 4430(March). https://doi.org/10.1080/03004430.2015.1100175 Raj, A., & Kasi, S. (2015). International Journal of Disaster Risk Reduction Psychosocial disaster preparedness for school children by teachers. International Journal of Disaster Risk Reduction, 12, 119–124. https://doi.org/10.1016/j.ijdrr.2014.12.007 Raynaudo, G., & Peralta, O. (2019). Children learning a concept with a book and an e-book: a comparison with matched instruction. European Journal of Psychology of Education, 34(1), 87–99. https://doi.org/10.1007/s10212-018-0370-4 Sawyer, B., Atkins-burnett, S., Sandilos, L., Hammer, C. S., Lopez, L., Blair, C., ... Hammer, C. S. (2018). Variations in Classroom Language Environments of Preschool Children Who Are Low Income and Linguistically Diverse. Early Education and Development, 29(3), 398– 416. https://doi.org/10.1080/10409289.2017.1408373 Simcock, G., & Heron-delaney, M. (2016). Infant Behavior and Development Brief report Reality check : Prior exposure facilitates picture book imitation by 15-month-old infants. Infant Behavior and Development, 45, 140–143. https://doi.org/10.1016/j.infbeh.2016.09.003 Solfiah, Y., Risma, D., & Kurnia, R. (2019). The Knowledge Of Early Childhood Education Teachers About Natural Disaster Management. 2(1), 159–166. Sugiyono. (2017). Metode Penelitian dan pengembangan, untuk bidang pendidikan,manegement sosial. Bandung: alfabeta. Sumantri, M. S. (2015). Strategi Pembelajaran. Jakarta: Raja Grafindo Persada.Suryaningsih, E., & Fatmawati, L. (2017). Pengembangan BUku Cerita Bergambar Tentang Mitigasi Bencana Erupsi Gunung Api Untuk Siswa SD. Profesi Pendidikan Dasar. Tatebe, J., & Mutch, C. (2015). International Journal of Disaster Risk Reduction Perspectives on education , children and young people in disaster risk reduction. International Journal of Disaster Risk Reduction, 1–7. https://doi.org/10.1016/j.ijdrr.2015.06.011 Tomé-Fernández, M., Senís-Fernández, J., & Ruiz-Martín, D. (2019). Values and Intercultural Experiences Through Picture Books. Reading Teacher, 73(2), 205–213. https://doi.org/10.1002/trtr.1813 Torani, S., Majd, P. M., Maroufi, S. S., Dowlati, M., & Sheikhi, R. A. (2019). The importance of education on disasters and emergencies: A review article. Journal of Education and Health Promotion, Vol. 8, p. 85. https://doi.org/10.4103/jehp.jehp_262_18 Tuladhar, G., Yatabe, R., Bhandary, N., & Dahal, R. (2015). Assessment of disaster risk reduction knowledge of school teachers in Nepal. International Journal of Health System and Disaster Management, 3(1), 20. https://doi.org/10.4103/2347-9019.147142 Undang-undang No. 24 Tahun 2007 Tentang Penanggulangan Bencana , (2007).